Respostas fisiológicas e bioquímicas do jeju Hoplerythrinus unitaeniatus (Characiformes, Erythrinidae) a exposição aérea - Mariano, Wagner dos Santos (2006)
The physiological and biochemical responses to air exposure were analyzed in jeju, Hoplerythrinus unitaeniatus at 1(T1), 6 (T6) and 12 (T12) hours of exposure and 1 (TR1) e 6 (TR6) hours after returning to water environment. Plasma cortisol and glucose were significantly higher than those of control group (T0) after 1 and 6 hours and 1, 6 and 12 hours of air exposure, respectively. Acid-base and ionic unbalances during air exposure were evidenced by plasma pH and Na+ and K+ concentration following pH recovery as fish returned to water environment. Ammonia accumulation was found in all experimental groups increasing continuously during air exposure (from 102.20 nmol/mL in T0 to 339.53 nmol/mL in T12). During the recovery period in water there was a reduction in plasma ammonia concentration but it was significantly higher than the controls. Plasma lactate showed a slightly increase during air exposure and was significantly higher than the controls only 1 hour after recovery in water (from 4115.42 nmol/mL in T0 to 6423.84 nmol/mL in TR1) while piruvate increased after 6 hour in water (from 171.87 nmol/mL in T0 para 243.96 nmol/mL in TR6). Hematocrit, red blood cells, hemoglobin concentration and mean corpuscular hemoglobin concentration increased significantly during air exposure. On the first hour of air exposure the lipid hydroperoxide (HP) increased. There was a reduction of catalase (CAT) and superoxide dismutase (SOD) activity and an increase of glutathione peroxidase (GPX) during air exposure. Air exposure can be characterized as an stressor agent to H. unitaeniatus and imply in physiological adjustments to keep the O2 transfer from air to tissue and homeostasis as well as energy mobilization.